From James Bond with love: tourism and tourists in the Bond saga - Marie-Hélène Chevrier; Chloé Huvet (Via@)
‘We could meet at the Saint Sophia mosque. – Like we were tourists,’ suggests James Bond to Russian agent Tatiana Romanova in From Russia with Love. Since 1962 and the release of Dr. No, tourism and tourists have played an important role in the James Bond saga in terms of affording viewers some escapism. Each film turns into a picture postcard as it takes the hero off to new destinations. The Bond films play on archetypes of destination (which they reinforce) and of tourism practices. These archetypal representations, from mass tourism to luxury tourism and from collective practices to individual practices, are all linked in the films to the image and sound (music and sound design) environments. In this article, we highlight how the Bond saga reflects the evolution of the core tourism practices and representations in Western societies from the 1960s to the present day.